Coaches' use of need-supportive and need-thwarting behaviors across the developmental continuum: a qualitative investigation in figure skating - Benish, D.; Readdy, T.; Raabe, J. (International Sport Coaching Journal, 2024)
There is extensive evidence illustrating the influence of coach behavior on athletes` perceived basic psychological needs. However, much of that research has been conducted with athletes of similar developmental stages (i.e., children, adolescents, or adults). In sports such as figure skating, coach-athlete relationships often span several years and developmental stages; yet, researchers have not comprehensively investigated whether coaches consider athletes` physical, social, self, cognitive, and emotional development in their interpersonal style. The purpose of this study was to qualitatively explore (a) what need-supportive and/or need-thwarting behaviors coaches use with athletes in different developmental age groups and (b) whether coaches` use of need-supportive and need-thwarting behaviors was developmentally appropriate based on theoretical implications and empirical evidence grounded in both developmental and self-determination theory. Semistructured interviews were conducted with 13 coach-athlete dyads (13 coaches and 13 athletes) across four age groups: middle childhood (6-10 years), early adolescent (11-14 years), mid-adolescent (15-17 years), and early adulthood (18-25 years). Deductive reflexive thematic analysis of the 26 interviews revealed four themes highlighting (a) competence-supportive, (b) autonomy-supportive, (c) relatedness-supportive, and (d) need-thwarting behaviors. There were both consistencies and variations in coaches` use of those behaviors across the four age groups.